Backstepping sliding-mode control for active suspension system matching mechanical elastic wheel with uncertainties. (October 2022) - Xu, Tao; Zhao, Youqun; Lin, Fen; Wang, Qiuwei
For the purpose of anti-puncture and lightweight, a new type of mechanical elastic wheel (MEW) is constructed. However, the large radial stiffness of MEW has a negative effect on ride comfort. To make up for the disadvantage, this paper proposes a novel control strategy consisting of backstepping control and integral sliding-mode control, considering the uncertainties of active suspension and MEW. First, an active suspension system matching MEW is established, discussing the impact of uncertainties. The nonlinear radial characteristic of MEW is fitted based on the previous experiment results. Then, in order to derive ideal motions, an ideal suspension system combining sky-hook and ground-hook damping control is introduced. Next, ignoring the nonlinear characteristics and external random disturbance, a backstepping controller is designed to track ideal variables. Combined with the backstepping control law, an integral sliding-mode control strategy is given, further taking parameter uncertainty and external disturbance into account. To tackle chattering problem, an adaptive state variable matrix is applied. By using Lyapunov stability theory, the whole scheme proves to be robust and convergent. Finally, co-simulations with Carsim and MATLAB/Simulink are carried out. By analyzing the simulation results, it can be concluded that the vehicle adopting backstepping sliding-mode control performs best, with excellent real-time performance and robustness.